Maternal and child health strategy for the Caribbean Community (PAHO Christ ChurchBB, 1993)
Sets out the strategic approach within the human development cycle, starting with the women's reproductive health moving through pregnancy, then focussing on the infant and pre-school child, the school child and the adolescent. Examines essential supporting mechansisms as well.
Bibliography: p.91